Subcutaneous Emphysema Induced by Cryotherapy: A Complication due to Previous Punctures - Jared Martínez-Coronado; Bertha Torres-Álvarez; Juan Pablo Castanedo-Cázares (Case Reports in Dermatological Medicine)
Cryosurgery is a common therapeutic modality used in dermatology; therefore we must be aware of its possible adverse effects. We report a case of a patient with subcutaneous emphysema which occurred following the application of cryotherapy after multiple punctures of local anesthetic and intralesional steroids in a chest keloid scar. Despite the fact that this condition was gradually resolved after expectant observation, we warn about this complication when sprayed cryotherapy is preceded by multiple punctures on cutaneous lesions above bony surfaces. In similar settings, cryotherapy must be first administered or a cotton-tip applicator should be used.